IMPLEMENTASI METODE MAUT DALAM PENILAIAN KINERJA PRAMUNIAGA PADA TOKO ARIF JAYA AIR JOMAN - Fahira, Aulia; Handayan, Masitah; Latiffani, Chitra (JIPI (Jurnal Ilmiah Penelitian dan Pembelajaran Informatika), 2025)
The Arif Jaya Air Joman shop is still manual, namely a system of recording in books when searching for data, so it experiences difficulties. The same thing also applies to evaluating the performance of sales assistants, they still use an observation system, which of course takes a long time and the assessment becomes less objective, because it is not based on calculating the proper criteria. So we need a decision-making system that can carry out the salesperson performance assessment process. To get the best alternative for salesperson performance assessment, start by determining the normalization matrix which functions to influence the performance assessment and the calculation results of the Multi Attribute Utility Theory (MAUT) method by multiplying the weight of each predetermined criterion. The aim of these results is to evaluate the performance of the sales assistants and provide rewards in the form of bonuses or salary increases to the best sales assistants to stimulate performance